2018
DOI: 10.1108/jadee-08-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

A parametric test evaluating smallholder farmers’ training needs in Uganda

Abstract: Purpose Effective rural agribusiness development requires dedicated training programmes therefore, this paper is an attempt to investigate smallholder farmers’ TNs in the dairy agribusiness sector. The purpose of this paper is to study a bigger research project of the dairy value chain in agribusiness framework in the Rwenzori region. Design/methodology/approach A sample size of 100 dairy farmers were randomly selected from two Districts in the Rwenzori region. The descriptive statistics (mean and standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
4
9
0
1
Order By: Relevance
“…This means that the training needs of female paddy farmers will not change with increase or decrease in age, number of dependents, work experience, and rice yield. These findings are in line with the findings of the studies by Hashemi et al [37] and Kataike et al [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This means that the training needs of female paddy farmers will not change with increase or decrease in age, number of dependents, work experience, and rice yield. These findings are in line with the findings of the studies by Hashemi et al [37] and Kataike et al [38].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, training needs assessment by an agricultural agent is necessary before launching training-extension courses. The research conducted by Olorunfemi et al [40] showed that the main job had no effect on the amount of training needs, but the study conducted by Kataike et al [38] showed that the main job had an effect on the number of training needs, which was also approved in the present study. A study by Man et al [24] found that the primary form of work has a favorable and important impact on agricultural extension agents' training needs.…”
Section: Discussionsupporting
confidence: 66%
“…Uganda's agricultural sector is majorly comprised of crop husbandry and livestock farming. According to Kataike et al (2018) and Uganda Export Promotion Board (2013), the government of Uganda, in an attempt to promote diversification in its trade pattern, emphasized value addition to dairy products in order to enhance trade performance of the country. Uganda's dairy industry has bucked a trend in the agricultural sector in which production grew very slowly since the late 1990s and was less than 1% in 2010/2011.…”
Section: Study Settingmentioning
confidence: 99%
“…The second relates to high milk spoilage and poor-quality milk because of lack of cooling facilities and high electricity costs to keep the milk in cold conditions. Kataike et al (2018) and Uganda Export Promotion Board (2014) make conservative estimates of about 80% of the milk produced to be sold through informal market channels mainly by small-scale farmers owning over 90% of the cattle population of country. According Kataike et al (2018) and DDA (2010), the milk industry in Uganda is highly skewed comprising 1m smallholders, 10,000 of middlemen with least agents in the milk supply chain being processors and exporters.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation